ANALISIS YURIDIS PASAL 1320 KUHPERDATA TERHADAP PERJANJIAN KERJASAMA LINGGA JAYA KONSTRUKSI DENGAN SUB KONTRAKTOR MITRA DINAMIS - Usnita, Usnita; Ukas, Ukas (SCIENTIA JOURNAL, 2020)
The agreement is the beginning of an agreement on a work agreed between the two parties that contains the rights and obligations of one party to another that binds itself and agrees to the agreement. This study raised and discussed the legal agreement between PT. Lingga Jaya construction with Mitra dynamic. All forms of agreements and commitments arising from agreements on a work agreed by the parties that bind themselves are born and contained in a contract that depends on the type of work to be performed by the parties. the purpose of this research is to find out the Implementation of Article 1320 of the Criminal Procedure Code and Article 1313 of the Criminal Procedure Code on cooperation agreements on rights and obligations between PT. LINGGA JAYA CONSTRUCTION with CV. Dynamic Partners. This research is an empirical legal research that is legal research that uses empirical facts taken from human behavior, both verbal behaviors obtained from interviews and real behavior carried out through direct observation. This data collection technique is the author plunged directly into the place to be examined by researchers to find the data needed by interview.